Retrospective Evaluation of the Implementation of Community Activity Restrictions in Ambon City - Jusuf madubun; Josep Antonius Ufi; Hadijah Madubun; Rizki Muhammad Ramdhan; Suleman Watianan (Journal of Governance, 2023)
This study aims to evaluate the implementation of policies regarding the imposition of community activity restrictions during the pandemic in Ambon City. The method used in this research is qualitative-descriptive with a retrospective policy analysis approach. The research results indicate that the implementation of community activity restrictions in Ambon City is not fully effective due to the mismatch between on-ground implementation and the regulations set by the government. Restrictions on community activities that impact the reduction of human contact intensity in public spaces and the use of masks are not new, and humans have endeavoured to implement these measures when dealing with similar cases like the Spanish Flu and COVID-19 in two different periods. Observing the repeating patterns of major cases that are highly likely to occur again in the future, the model of implementing restrictions on community activities, with its refinements, can be considered an example of controlling emergency problems of epidemic outbreaks and other health disasters with rapid spread and highly destructive impacts.